2018
DOI: 10.1073/pnas.1717920115
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell analysis of endogenous GFP-RPB1 uncovers rapid turnover of initiating and promoter-paused RNA Polymerase II

Abstract: SignificanceTranscription by RNA Polymerase II (Pol II) is a highly dynamic process that is tightly regulated at each step of the transcription cycle. We generated GFP-RPB1 knockin cells and developed photobleaching of endogenous Pol II combined with computational modeling to study the in vivo dynamics of Pol II in real time. This approach allowed us to dissect promoter-paused Pol II from initiating and elongating Pol II and showed that initiation and promoter proximal pausing are surprisingly dynamic events, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
219
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(265 citation statements)
references
References 56 publications
(121 reference statements)
32
219
0
Order By: Relevance
“…To further explore the relationship between global chromatin dynamics and transcriptional activity, we examined the dynamics of RNA polymerase II (RPB1-Dendra2; RNA Pol II) in live U2OS cell nuclei ( Figure 4a) at different transcriptional states. Hi-D analysis resolved three mobility populations of RNA Pol II (Figure 4b), which is consistent with previous studies that revealed three kinetically different groups of RNA Pol II based on their chromatin-binding times [28,29]. The three dynamic populations in actively transcribing cells (grown in normal condition) exhibited significantly higher diffusion constants as in transcriptionally less active cells (serum-starved cells) ( Figure 4b).…”
Section: Transcription Status Modulates Chromatin Diffusion Processessupporting
confidence: 89%
“…To further explore the relationship between global chromatin dynamics and transcriptional activity, we examined the dynamics of RNA polymerase II (RPB1-Dendra2; RNA Pol II) in live U2OS cell nuclei ( Figure 4a) at different transcriptional states. Hi-D analysis resolved three mobility populations of RNA Pol II (Figure 4b), which is consistent with previous studies that revealed three kinetically different groups of RNA Pol II based on their chromatin-binding times [28,29]. The three dynamic populations in actively transcribing cells (grown in normal condition) exhibited significantly higher diffusion constants as in transcriptionally less active cells (serum-starved cells) ( Figure 4b).…”
Section: Transcription Status Modulates Chromatin Diffusion Processessupporting
confidence: 89%
“…To strength our proposal, we treated cells with a CDK7 inhibitor THZ1, which suppresses initiation and pausing (Kwiatkowski et al , ; Steurer et al , ). THZ1 treatment markedly decreased heat shock‐induced expression of HSP70 mRNA (Appendix Fig S6E).…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy may be explained by recent experiments, including live imaging in vivo which showed that most 5' bound Pol II is rapidly turned over (Erickson et al 2018;Kamieniarz-Gdula and Proudfoot 2019;Steurer et al 2018) This could be associated with cycles of abortive initiation rather than stable pausing. Over time, such transiently associated Pol II may be detected by ChIP but would not necessarily produce scaRNAs which require transcriptionally engaged Pol II.…”
Section: Discussionmentioning
confidence: 97%
“…As turnover of Pol II during recruitment/initiation is approximately two orders of magnitude faster than in gene bodies (J. Li et al 2019;Steurer et al 2018) this could result in a higher level of fixation in promoter versus gene bodies resulting in skewed increases in pausing indices which does not truly reflect the process of transcription which is readily seen using scaRNAseq and nascent-RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation